Learner Autonomy, Self Regulation and Metacognition - Feryal CUBUKCU (International Electronic Journal of Elementary Education, 2009)
Different theories try to explain why some students are more successful than the others. Phenomenologists (Mc Combs, 1989) study self concepts of the students and find such students prone to achieve more. Attributional Theorists (Dweck, 1986; Weiner, 2005) focus on personal outcome such as effort or ability. Metacognitive theorists (Pressley, 2000; Schunk, Pintrich & Meece, 2007) examine students’ self regulated learning strategies whereas Constructivists (Maxim, 2009; Paris & Byrnes, 1989) believe supportive environments are important to be successful. In this study, the metacognitive theory will be given more importance and the purpose of the article is to find the correlation between self regulation, metacognition and autonomy.